Predictors of Poor Sleep Quality among Vegetarians: Insights from a Study in Kuala Lumpur and Selangor, Malaysia - Ching, Yuan Kei; Chin, Yit Siew; Appukutty, Mahenderan; Chan, Yoke Mun; Lim, Poh Ying (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study aimed to examine the prevalence of poor sleep quality and its predictors among Malaysian vegetarians. The present cross-sectional study was conducted among 200 vegetarians in Malaysia. Data on socio-demographic characteristics, lifestyle behaviours, psychological distress and sleep quality were collected using a set of self-administered questionnaires. A three-day dietary recall was employed to examine the dietary intake of vegetarians. The Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality in vegetarians, with a score above five indicating poor sleep quality. A multiple logistic regression model was used to determine how socio-demographic characteristics, lifestyle behaviours (smoking, alcohol consumption and physical activity level), psychological distress (depression, anxiety, and stress) and specific dietary macronutrient intakes (carbohydrate, protein and fat) predicted poor sleep quality. The mean sleep duration was 6.0±1.4 hours among vegetarians. The mean PSQI score was 5.4±3.1, with 40.5% of vegetarians experiencing poor sleep quality. Multiple logistic regression found that vegetarians with depression (OR=4.56, 95% CI:1.62‒12.83) and stress (OR=3.07, 95% CI: 1.14‒8.31) had higher odds of poor sleep quality (p<0.05). About two in five (40.5%) vegetarians reported poor sleep quality with depression and stress as significant predictors. Effective sleep education programs are essential for improving sleep hygiene awareness. Psychological screening and mental health interventions for vegetarians with depression and stress are necessary to improve their sleep health.